Analisis penentuan harga pokok produksi menggunakan metode full costing dan variable costing dalam penetapan harga jual Sambal Roa Chef Kenneth (Studi pada UD Cinta Kasih Manado) - Rembet, Jillsticia; Tirayoh, Victorina Z.; Kalalo, Meily Y. B. (Yayasan Widyantara Nawasena Raharja, 2024)
UD Cinta Kasih Manado is a business that processes and produces garfish chili sauce. UD Cinta Kasih is still calculating the cost of production in determining product selling prices in a simple way, not yet classifying costs according to cost elements. The aim of this study is to determine the calculation of the cost of production using full costing and variable costing methods in determining the selling price of “Sambal Roa” by Chef Kenneth. The method used is descriptive qualitative with data collection through interviews. The results show that the calculation of the cost of production according to UD Cinta Kasih produces different results from calculations using the full costing and variable costing methods. The difference in value is obtained because the company's method only includes some factory overhead costs in calculating the cost of production. Calculation of the cost of production using the full costing method produces higher results than calculation results using the variable costing method. This is because in calculations using the variable costing method, fixed factory overhead costs are not taken into account. UD Cinta Kasih should apply the full costing method to calculate the cost of production in determining selling prices. The full costing method takes into account all costs related to the production process, thereby helping to implement resource efficiency in production activities, preventing the risk of loss, and for long-term profit planning.